Celiac Disease Diagnosis Via Histopathological Correlation of Duodenal Biopsies in Children - Muhammad Sami Ullah, Maira Angbeen, Amna Tanvir, Muhammad Haidar Zaman, Sohail Hussain, Urwa Sarwar, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The purpose of this study is to compare the diagnostic accuracy of duodenal bulb biopsies to distal duodenal biopsies in patients suspected of having celiac disease. Study Design: Cross-sectional study Place and Duration: This study was conducted at Department of Pathology, The children's hospital & The institute of child health, Multan during the period from April, 2022 to September, 2022. Methods: Total 86 children of celiac disease were presented in this study. Informed written consent provided by parents of children for the collection of detailed demographic data. Under general anaesthesia, a duodenal bulb sample and four distal duodenum samples were collected during an upper gastrointestinal endoscopy. Histological alterations indicative with CD were identified. Histological diagnosis and grading were performed using a modification of the Marsh-Oberhuber classification. The entire data set was analyzed by using SPSS 20.0. Results: Forty nine (56.97%) patients were females and 37 (43.03%) cases were males. Children’s mean age was 6.4±3.27 years with mean weight 15.9±6.19 kg. Mean height of the cases was 94.7±10.42 cm. There were 51 (59.3%) children had urban residency. According to marsh grading, 50 (58.1%) cases had grade IIIC. We found that frequency of crypt hyperplasia, influx of immune cells in lamina propria and enterocytes change in both duodenal bulb and distal part biopsies were equal while only frequency of villous atrophy and intraepithelial lymphocytes were different in both biopsies. 96.5% patients reported a high level of correlation, while only 3.5% reported no correlation. Conclusion: Both biopsy sites agree strongly. We may now suggest duodenal bulb biopsy alone. Since the endoscopic method of distal duodenum is laborious and requires more knowledge and time, obtaining biopsies from the proximal section is easier and requires less experience, therefore this strategy may be used even at facilities with junior paediatric gastroenterologists. Keywords: Celiac disease, Children, Histopathology, Duodenal bulb, Distal duodenum